Гігієнічна оцінка та профілактика впливу атмосферних забруднень на населення у мегаполісі металургійної галузі - Федорченко, Руслана Анатоліївна; Fedorchenko, R. A. (Харківський національний медичний університет, 2016)
В дисертації обґрунтовано принципи профілактики несприятливого впливу забруднення атмосферного повітря на здоров’я мешканців у промисловому місті металургійної галузі шляхом удосконалення гігієнічної донозологічної діагностики хвороб органів дихання, алергійного стану органів дихання, імунного й вітамінного статусу, біоіндикаторів атмосферних забруднень. Надана ризикометрична оцінка впливу атмосферних забруднень на стан здоров’я населення індустріального міста на основі визначення детермінантних чинників, відносного й атрибутивного ризиків; проведено порівняльний аналіз закономірностей забруднення атмосфери, стану здоров’я на нозологічному й донозологічному рівнях та ризикометричних досліджень, на основі яких обґрунтовано принципи первинної, вторинної і третинної профілактики, спрямовані на збереження здоров’я населення. Результати роботи впроваджено в практичну діяльність ДУ «Головне управління Держсанепідслужби в Запорізькій області»; ДУ «Одеське міське управління Головного управління Держсанепідслужби в Одеській області»; ДУ «Запорізький обласний лабораторний Центр»; ДУ «Одеський обласний лабораторний Центр»; Управління з питань охорони здоров’я Запорізької міської ради; Управління з питань екологічної безпеки Запорізької міської ради; в навчальний процес викладання дисципліни загальна гігієна та екологія в ЗДМУ, ОдНМУ, ЗНУ. Scientifically substantiated and experimentally proved complex identification of toxic substances emissions from stationary and mobile sources, concentrations of harmful chemicals in the air; assess the risks of exposure to air pollution on the health of the population of a large industrial city on the basis of the definition of determinant factors relative calculations, attributive and population risks identified regularities of vitaminosis - to 25,2-34,5% (p<0,01). morbidity and mortality in the class of respiratory diseases due to exposure to industrial emissions of the metallurgical industry, as well as their forecasting through the development of statistical regression-turn-based models; substantiated hygienic preclinical diagnosis of respiratory diseases as a result of research and the establishment of spirographic obstructive-restrictive disorders bronchopulmonary apparatus residents of different areas of the city, studying allergic condition of the respiratory, immune and vitamin status, bioindicators of air pollution. A comparative analysis of laws atmospheric pollution on the health of nosological and preclinical levels using a risk assessment methodology, based on which justified the principles of primary, secondary and tertiary prevention aimed at preserving the health of the population of the metropolis. Based on the identification of air pollution from stationary and mobile sources, the definition of determinant risk factors for health, hygiene preclinical diagnosis and patterns of morbidity reasonably 7 principles of primary and secondary prevention and tertiary prevention principle 3. Implementation of the development of preventive measures yielded a positive effect: total emissions decreased by 9,7%, emissions of solids – 10,4%, gas - by 4,7%. Medical and social effect was to increase the health index at 4,5-4,7% (p<0,01), saliva lysozyme - at 0,77-0,86 g/ml (p<0,05), with a decrease prevalence polyhypovitaminosis - to 25,2-34,5% (p<0,01).
Hygienic assessment and prevention of the effects of atmospheric pollution on the population in the city of metallurgical industry
Keywords: атмосферне забруднення; викиди; здоров’я населення; ризики; донозологічний стан; air pollution; emissions; population health; health risks; prenosological state